Design, Fabrication, and Testing of Prototype of Total Lumbar Disc Replacement - Rela Adi Himarosa; Suyitno Suyitno (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2018)
Total Disc Replacement (TDR) implant is part of the prosthesis to treat degenerative disease by retaining the maneuverability of the disk itself. The TDR implant allows to repair the movement of the spines, absorbs the friction of intervertebral discs, and restore the height of the vertebrae. In this study, we constructed a new model of TDR implant, which is feasible to be mass-produced in Indonesia and performed static test to examine the mechanical properties of the new model. Before starting the prototype production, the finite element simulation is necessary. Simulation using Abaqus 6.14 software show that our design is safe from mechanical failure. The simulation test was performed using the static general model, non linear by considering the plasticity of UHMWPE material. Manufactured using CNC 3 Axis and the prototype was tested with ASTM 2077 standards, using two calibration model on horizontal position and tilted position of 27° to measure the compressive strength and shear strength respectively.